Xukuru-Kariri Indigenous Land: advances and setbacks / Terra Indígena Xukuru-Kariri: avanços e recuos - Maria Ester Ferreira da Silva Viegas (Universidade Estadual de Alagoas, 2019)
We will try to approach in this paper how the socials actors (in the Xukuru-Kariri's case) of Palmeira do Índios/AL became excluded from the so called "big political pact of Brazilians elites" and how they organize themselves as a group so to do against the landlords. The landlords, who had the State as guarantor of them economic power, prevent that the peasantry whether indigenous or not, disturb the schemes of iron logic of the developmental economism. The discussion about the disintegration of indigenous lands in Brazil is the central concern of those who study about the agrarian question. The more current discussion shows the intensity and centrality of agrarian question in the social and political though in Brazil. It is also true that this discussion reflects a lot of historical and economical current conjuncture where contextualizes the speech and as how they analyze the social actors involved in the Brazilian agrarian process. The Xucuru-Kariri people from a movement of land (re)occupation triggers a process of reinforce and reformulation in his ethnical identity, aiming to expend of his political space.